Hydrogen Gas in Cancer Treatment - Li, Sai; Liao, Rongrong; Sheng, Xiaoyan; Luo, Xiaojun; Zhang, Xin; Wen, Xiaomin; Zhou, Jin; Peng, Kang (Frontiers in Oncology, 2019)
Gas signaling molecules (GSMs), composed of oxygen, carbon monoxide, nitric oxide, hydrogen sulfide, etc., play critical roles in regulating signal transduction and cellular homeostasis. Interestingly, via various administrations, these molecules also exhibit potential in cancer treatment. Recently, hydrogen gas (formula: H2) emerges as another GSM which possesses multiple bioactivities, including anti-inflammation, anti-reactive oxygen species, and anti-cancer. Growing evidence has shown that hydrogen gas can either alleviate the side effects caused by conventional chemotherapeutics, or suppress the growth of cancer cells and xenograft tumor, suggesting its broad application potential in clinical therapy. In the current review, we summarize these studies and discuss the underlying mechanisms. The application of hydrogen gas in cancer treatment is still in its nascent stage, further mechanistic study and development of portable instruments are warranted.